A large carotid body tumour: a rare case report - Shankar, Mrinal; Saini, Sunil; Pattanayak, Manisa (International Surgery Journal, 2017)
Carotid body tumour (CBT) is one of the most common jugular paraganglioma involving the carotid body chemoreceptors. We report the case of a 22 year young man who presented with complain of large painless progressive swelling in right upper neck for 3 years duration. On examination, swelling appeared pulsatile and arising from carotid vessel. MRI Neck and MRA performed revealed large well defined hypervascular mass lesion encasing right common carotid artery, its bifurcation and ECA, with feeders from ECA. Patient was undertaken for surgical excision (Shamblin Grade-III) through exposure in neck, extended by midline sternotomy and mandibulotomy approach, tumour was completely dissected. Patient recovered well from surgery without any sequale. HPE revealed CB paraganglioma. At two years follow up, he is recurrence free. The surgical removal of CBT has a good result.